2021
DOI: 10.1007/s10534-021-00348-3
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Sucrosomial® iron leads to favourable changes in the intestinal microbiome when compared to ferrous sulfate in mice

Abstract: Iron deficiency is one of the most common nutritional deficiencies worldwide and is often treated with oral iron supplements. However, commonly used supplements, including those based on ferrous iron salts, are associated with gastrointestinal side effects and unfavorable changes in the intestinal microbiome. Sucrosomial® iron is a novel iron formulation that is effective at treating iron deficiency, and with fewer gastrointestinal side effects, yet its effect on the gut microbiome has not been examined previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…The changes in bacterial abundance at the phylum and genus levels at both ages imply potential adverse effects to health [ 67 ]. The differential effects of FS and FC on gut bacterial abundance align with recent evidence that the form of iron is relevant when considering health outcomes of iron provision [ 75 , 76 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The changes in bacterial abundance at the phylum and genus levels at both ages imply potential adverse effects to health [ 67 ]. The differential effects of FS and FC on gut bacterial abundance align with recent evidence that the form of iron is relevant when considering health outcomes of iron provision [ 75 , 76 ].…”
Section: Discussionsupporting
confidence: 73%
“…A recent study in adult mice found that microbiome Shannon diversity effects differed according to iron form—FS or Sucrosomial ® iron—but observed that species richness increased similarly. A reduction in Lactobacillaceae was observed only in Sucrosomial ® iron-treated mice [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parabacteroides ( 62 ), Alistipes and Odoribacter ( 63 ) modulate metabolism and produce SCFAs. Here, L. paracasei administration increased the abundance of SCFA-producing bacteria including Oscillibacter ( 64 ), Roseburia , Odoribacter , and Alistipea .…”
Section: Discussionmentioning
confidence: 93%
“…Heme may favor the growth of Akkermansia muciniphila, a mucin-degrading bacterium, which may lead to disruption of the mucus barrier [135]. Nevertheless, there is evidence suggesting that iron supplementation may be beneficial for the microbiome depending on formulation [136,137]. Additional studies would be needed to evaluate the impact of dietary or various forms of supplementary iron on the intestinal microbiome in the general population and in specific patient groups.…”
Section: Iron and The Intestinal Microbiomementioning
confidence: 99%